2015
DOI: 10.1152/jn.00276.2015
|View full text |Cite
|
Sign up to set email alerts
|

Eye-hand coordination during a double-step task: evidence for a common stochastic accumulator

Abstract: Many studies of reaching and pointing have shown significant spatial and temporal correlations between eye and hand movements. Nevertheless, it remains unclear whether these correlations are incidental, arising from common inputs (independent model); whether these correlations represent an interaction between otherwise independent eye and hand systems (interactive model); or whether these correlations arise from a single dedicated eye-hand system (common command model). Subjects were instructed to redirect gaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 46 publications
3
23
0
Order By: Relevance
“…These findings are consistent with previous research suggesting both effector-dependent andindependent movement planning processes. As mentioned in the introduction, a number of studies have shown strong correlations between initiation times of the eye and the hand, consistent with a shared movement planning stage (Biguer, Jeannerod, & Prablanc, 1982;Bekkering et al, 1995;Gopal & Murthy, 2015;Lee et al, 2014;Neggers & Bekkering, 1999;Sailer et al, 2000;Suzuki, Izawa, Takahashi, & Yamazaki, 2008;Tao, Khan, & Blohm, 2018). An effector-independent stage reflecting shared outcomes for different effectors has been suggested previously in terms of a shared target selection stage for both the eye and the hand (Song & McPeek, 2009).…”
Section: Discussionmentioning
confidence: 59%
“…These findings are consistent with previous research suggesting both effector-dependent andindependent movement planning processes. As mentioned in the introduction, a number of studies have shown strong correlations between initiation times of the eye and the hand, consistent with a shared movement planning stage (Biguer, Jeannerod, & Prablanc, 1982;Bekkering et al, 1995;Gopal & Murthy, 2015;Lee et al, 2014;Neggers & Bekkering, 1999;Sailer et al, 2000;Suzuki, Izawa, Takahashi, & Yamazaki, 2008;Tao, Khan, & Blohm, 2018). An effector-independent stage reflecting shared outcomes for different effectors has been suggested previously in terms of a shared target selection stage for both the eye and the hand (Song & McPeek, 2009).…”
Section: Discussionmentioning
confidence: 59%
“…The stochastic independence of the GO and STOP processes can be tested qualitatively by comparing cumulative RT distributions of step error trials and no‐step trials (Boucher et al ., ; Kapoor & Murthy, ; Gopal & Murthy, ). If we assume an independent race model, it predicts an ordering of cumulative RT distributions for step errors and no‐step trials; the distributions would have a common minimum and diverge at longer TSDs, with the error distribution to the left of the no‐step RT distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Subjects were monetarily rewarded for their participation and for every correct trial to keep them motivated to do the task. Part of the data (eight of 24 subjects) was already used elsewhere (Gopal & Murthy, ; Gopal et al ., ) for another purpose and was added to the dataset to further substantiate the generality of the results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 31 However, since we did not calculate the latency of the hand movements from the display of the visual target, it is not possible to determine whether this increased latency is a result of a delay in initiating the saccade or a delay in initiating the hand movement or both. Gopal and Murthy 32 in their study on latency of the saccades and hand motor system have documented the existence of a dedicated circuit for the EHC. Since there was a failure in reduction of saccadic latency in patients with WC during EHC, we propose that there may be an involvement of this circuit in WC patients.…”
Section: Discussionmentioning
confidence: 99%